Self-Check Teaching Style for Physical Education Teachers: A Literature Review - Abdhi, Muhammad Irwansyah; Kristiyandaru, Advendi; Priambodo, Anung (Prodi PGSD Penjas FPOK UPI, 2021)
Physical Education learning is sometimes perceived monotonous by students, especially when they only carry out movements according to the command of Physical Education teacher. The majority of students are also surfeited with Physical Education learning focusing on big ball games, such as soccer, volleyball, and basketball, especially for female students or those who have insufficient physical and sport skills. The innovation in Physical Education learning teaching styles is essential. The self-check teaching style in Physical Education learning has advantages, but it has not been widely applied by Physical Education teachers. This study was aimed at analyzing and reviewing the self-check teaching style. Therefore, the review method was chosen using a synthetic matrix analysis technique. Twelve national and international journals were selected from Google Scholar, Science Direct, and Research Gate websites based on self-check teaching style keywords. The results of the review found that the Self-Check teaching style had a positive effect and various benefits when it was applied by Physical Education teachers in the learning process. It recommends that further research, with a literature review model focusing on self-check teaching styles, to choose previous research focusing on certain subjects (1 subject) or a specific teaching material in certain subjects.